Polyether nitrile having improved crystallization rate, method for producing same, polyether nitrile resin composition, and method for producing same

By adjusting the molecular weight and molecular weight distribution of polyethernitrile and controlling its semi-crystallization time, the problem of slow crystallization speed of polyethernitrile is solved, and rapid crystallization and efficient forming are achieved.

CN119731238APending Publication Date: 2025-03-28HONSHU CHEM INDAL +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380062634.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-06
Filing Date
2023-08-04
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The crystallization rate of existing polyethernitriles is slow, which leads to the inability to sufficiently shorten the forming cycle during heating forming such as injection molding, affecting production efficiency.

Method used

By adjusting the molecular weight and molecular weight distribution of polyethernitrile, the specific method includes using polyethernitrile having a weight average molecular weight of 50,000 or more, and controlling the semi-crystallization time of polyethernitrile to be less than 100 seconds by the use of specific repeat unit structures and basic compounds.

Benefits of technology

The rapid crystallization of polyethernitrile is achieved, the forming cycle is shortened, the production efficiency is improved, and high heat resistance and mechanical strength are maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731238A_ABST
    Figure CN119731238A_ABST
Patent Text Reader

Abstract

The present invention addresses the problem of providing a polyethernitrile capable of improving the productivity of a molded article, the polyethernitrile being capable of solving the problem that a pure polyethernitrile exhibiting a semi-crystallization time of less than 120 seconds as regarded as a practical molding cycle has not yet been reported. As a solution, provided is a polyether nitrile characterized in that the half-crystallization time at 275 DEG C when the temperature is reduced from a molten state at 370 DEG C to 275 DEG C at a cooling rate of 500 DEG C per minute as determined by input compensation type differential scanning calorimetry is 100 seconds or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polyether nitrile having an excellent crystallization rate during molding, a method for producing the same, and a composition thereof. Background Art

[0002] Aromatic ether (co)polymers are not only excellent in heat resistance, flame retardancy, chemical resistance, and mechanical strength, but are also thermoplastic and can be formed by heating. Therefore, they are one of the useful resins that can be used to obtain various molded products such as wires, films, sheets, pipes, tubes, round rods, etc. through molding methods such as injection molding, extrusion molding, and heat compression molding.

[0003] Polyether nitrile (e.g., Patent Documents 1 to 4), which is one of the aromatic ether (co)polymers, has the highest level of heat resistance among thermoplastic resins and is excellent in mechanical strength. However, these polyether nitrile have a slow crystallization rate, so when a molded product is produced by hot molding such as injection molding, there is a problem that the molding cycle cannot be sufficiently shortened.

[0004] Therefore, attempts have been made to increase the crystallization rate of polyether nitrile by adding various crystal nucleating agents such as alumina, titanium dioxide, talc, and carbon black (for example, Patent Documents 5 and 6).

[0005] Furthermore, as a method for lowering the melting point while maintaining crystallinity, polyether nitrile obtained by using a small amount of a copolymerization component is disclosed (for example, Patent Document 7).

[0006] Patent Literature Patent Document 1: Japanese Patent Application Laid-Open No. 59-206433 Patent Document 2: Japanese Patent Application Laid-Open No. 60-147439 Patent Document 3: Japanese Patent Application Laid-Open No. 61-055120 Patent Document 4: Japanese Patent Application Laid-Open No. 62-223226 Patent Document 5: Japanese Patent Application Laid-Open No. 62-240353 Patent Document 6: Japanese Patent Application Laid-Open No. 01-193354 Patent Document 7: International Publication No. 2021 / 241492 Summary of the invention Pure polyether nitrile consisting only of polyether nitrile resin cannot achieve an increase in crystallization rate.

[0007] For example, the semi-crystallization times of the well-known polyether nitriles, namely, a polyether nitrile synthesized from resorcinol and 2,6-dichlorobenzonitrile (resorcinol-polyether nitrile), a polyether nitrile synthesized from hydroquinone and 2,6-dichlorobenzonitrile (hydroquinone-polyether nitrile), and a polyether nitrile synthesized from 4,4'-biphenylene glycol and 2,6-dichlorobenzonitrile (biphenylene glycol-polyether nitrile), at 280° C. were measured to be 120 seconds, 200 seconds, and 685 seconds, respectively (Patent Document 6), but there has been no report of a pure polyether nitrile showing a semi-crystallization time of less than 120 seconds, which is regarded as a practical molding cycle.

[0008] The polyether nitrile obtained by using a small amount of a copolymer component has a lower crystallization temperature than the polymer of a single component, but conversely the crystallization rate is also lower.

[0009] An object of the present invention is to provide a polyether nitrile which can solve these problems that have been conventionally encountered in polyether nitrile and has excellent heat resistance and mechanical strength, and can improve the productivity of molded products.

[0010] The present inventors have conducted intensive studies to solve the above problems and have found that polyether nitrile having a time required for crystallization within a specific range has an improved crystallization rate, and therefore can shorten the molding cycle when manufacturing a molded product by heat molding such as injection molding, thereby completing the present invention. It has also been found that sufficient mechanical strength can be obtained by setting the molecular weight within a specific range, and as described in the Examples below, by understanding the relationship between the isothermal crystallization temperature, the time required for crystallization, and the molecular weight and molecular weight distribution of the polyether nitrile, the polyether nitrile that meets the specific conditions has an excellent crystallization rate.

[0011] The present invention is as follows.

[0012] 1. A polyether nitrile characterized in that the half crystallization time at 275°C when cooled from a molten state of 370°C to 275°C at a cooling rate of 500°C per minute as determined by input compensation differential scanning calorimetry is 100 seconds or less.

[0013] 2. The polyether nitrile according to 1., wherein the polystyrene-equivalent weight average molecular weight (Mw) measured by gel permeation chromatography is 50,000 or more.

[0014] 3. The polyether nitrile according to 2., characterized in that the weight average molecular weight (Mw) and number average molecular weight (Mn) in terms of polystyrene measured by gel permeation chromatography analysis satisfy the formula (i), Formula (i): Mw / Mn≧2.4×10 -4 ×Mw-11.8.

[0015] 4. The polyether nitrile according to any one of 1. to 3., characterized in that the polyether nitrile has a repeating unit represented by the general formula (3), [Chemistry 1]

[0016] In the formula, R represents a divalent group represented by the general formula (1a) or the general formula (1b), and r represents an integer of 1 to 4. [Chemistry 2]

[0017] In the formula, R 1 Each independently represents a linear or branched alkyl group having 1 to 6 carbon atoms, a cyclic alkyl group having 5 or 6 carbon atoms, or a phenyl group, m each independently represents an integer of 0 to 4, n represents 0 or 1, p and q represent 0, 1 or 2, and * each represents a bonding position, [Chemistry 3]

[0018] In the formula, R 1 and m is the same as defined in the general formula (1a), Y represents an oxygen atom, a sulfur atom, a sulfonyl group, a carbonyl group, an alkylidene group having 1 to 15 carbon atoms, a fluorine-containing alkylidene group having 2 to 15 carbon atoms, a cycloalkylidene group having 5 to 15 carbon atoms, a phenylmethylidene group, a phenylethylidene group, a phenylene group or a fluorenylidene group, Z represents an oxygen atom, a sulfur atom or is unbridged, Ar each independently represents an aryl group having 6 to 8 carbon atoms, and * each represents a bonding position.

[0019] 5. The polyether nitrile according to 4., characterized in that R in the general formula (3) is the general formula (1a') or the general formula (1a"), [Chemistry 4]

[0020] In the formula, R 1 , m and * are the same as those defined in the general formula (1a), [Chemistry 5]

[0021] In the formula, R 1 , m and * are the same as defined in the above general formula (1a).

[0022] 6. The polyether nitrile according to 5., characterized in that the repeating unit represented by the general formula (3) is a repeating unit represented by the general formula (3'), [Chemistry 6]

[0023] In the formula, R has the same definition as in the general formula (3).

[0024] 7. The polyether nitrile according to 6., characterized in that R of the repeating unit represented by the general formula (3') is at least one group selected from the divalent groups represented by the following structures: [Chemistry 7] .

[0025] 8. A polyether nitrile resin composition, characterized in that it contains the polyether nitrile described in 1 and at least one of (A) to (C) selected from the group consisting of a thermoplastic resin material (A), an additive (B), and a filler (C).

[0026] 9. A method for producing the polyether nitrile according to 1., characterized in that two or more raw material polyether nitriles having different weight average molecular weights are mixed.

[0027] 10. The method for producing a polyether nitrile according to 9., wherein the polyether nitrile has a repeating unit represented by the general formula (3): [Chemistry 8]

[0028] In the formula, R represents a divalent group represented by the general formula (1a) or the general formula (1b), and r represents an integer of 1 to 4. [Chemistry 9]

[0029] In the formula, R 1 Each independently represents a linear or branched alkyl group having 1 to 6 carbon atoms, a cyclic alkyl group having 5 or 6 carbon atoms, or a phenyl group, m each independently represents an integer of 0 to 4, n represents 0 or 1, p and q represent 0, 1 or 2, and * each represents a bonding position, [Chemistry 10]

[0030] In the formula, R 1 and m is the same as defined in the general formula (1a), Y represents an oxygen atom, a sulfur atom, a sulfonyl group, a carbonyl group, an alkylidene group having 1 to 15 carbon atoms, a fluorine-containing alkylidene group having 2 to 15 carbon atoms, a cycloalkylidene group having 5 to 15 carbon atoms, a phenylmethylidene group, a phenylethylidene group, a phenylene group or a fluorenylidene group, Z represents an oxygen atom, a sulfur atom or is unbridged, Ar each independently represents an aryl group having 6 to 8 carbon atoms, and * each represents a bonding position.

[0031] 11. The method for producing a polyether nitrile according to 10., wherein the two or more raw material polyether nitriles having different weight average molecular weights are raw material polyether nitriles having the same repeating unit in the repeating unit represented by the general formula (3).

[0032] 12. A method for producing a polyether nitrile resin composition, characterized in that two or more raw material polyether nitrile materials having different weight average molecular weights are mixed with at least one selected from the group consisting of a thermoplastic resin material (A), an additive (B), a filler (C), and (A) to (C), wherein when the two or more raw material polyether nitrile materials are mixed, the polyether nitrile has a crystallization half time of 100 seconds or less at 275° C. when cooled from a molten state of 370° C. to 275° C. at a cooling rate of 500° C. per minute as determined by input compensation differential scanning calorimetry.

[0033] 13. The method for producing a polyether nitrile resin composition according to 12., characterized in that it comprises a polyether nitrile mixing step and a resin composition component mixing step, The polyether nitrile mixing step is a step of mixing the two or more raw material polyether nitriles having different weight average molecular weights to obtain a polyether nitrile, wherein the polyether nitrile has a crystallization half time of 100 seconds or less at 275° C. when cooled from a molten state of 370° C. to 275° C. at a cooling rate of 500° C. per minute as determined by input compensation differential scanning calorimetry. The resin composition component mixing step is a step of mixing the polyether nitrile obtained in the polyether nitrile mixing step with at least one selected from the group consisting of (A) to (C) of the thermoplastic resin material (A), the additive (B), and the filler (C).

[0034] Since the polyether nitrile of the present invention has an increased crystallization rate, it is not necessary to perform post-treatment such as annealing in heat molding such as injection molding of polyether nitrile having excellent heat resistance and mechanical strength, and a molded product can be obtained in a short molding cycle. In addition, since the crystallization rate can be increased by only containing a polyether nitrile resin component, there is no embrittlement problem compared to a conventionally known polyether nitrile resin composition to which a crystallization nucleating agent is added, and a polyether nitrile molded product having excellent mechanical strength can be provided.

[0035] The method for producing polyether nitrile of the present invention uses two or more raw material polyether nitriles having different weight average molecular weights and mixes them. The reaction time required for the production is short and reasonable, and the operation can be simple.

[0036] Since the polyether nitrile resin composition of the present invention uses the polyether nitrile of the present invention with a fast crystallization rate, a molded product of the polyether nitrile resin composition having excellent heat resistance can be obtained in a short molding cycle. In addition, the polyether nitrile resin composition of the present invention has a short and reasonable reaction time for production, and can also be produced industrially by simple operations. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1The graph shows the relationship between the molecular weight distribution (Mw / Mn) and the weight average molecular weight (Mw) of polyether nitrile, where Mw is in the range of 50,000 to 80,000 and Mw / Mn is in the range of 1 to 10, and the region of polyether nitrile having a semi-crystallization time of 100 seconds or less at a temperature of 275° C. is indicated by the shaded area with oblique lines. DETAILED DESCRIPTION

[0038] (Polyether nitrile of the present invention) The polyether nitrile of the present invention has a semi-crystallization time of 100 seconds or less at 275°C when cooled from a molten state of 370°C to 275°C at a cooling rate of 500°C per minute as measured by input compensation differential scanning calorimetry. The semi-crystallization time is preferably 85 seconds or less, more preferably 70 seconds or less, and particularly preferably 50 seconds or less. The shorter the semi-crystallization time, the faster the crystallization rate of the polyether nitrile, and thus the lower limit of the range is not particularly limited, but may be 1 second or more, preferably 10 seconds or more, from the viewpoint of productivity of the polyether nitrile molded product.

[0039] Input compensation differential scanning calorimetry is usually performed under a nitrogen atmosphere.

[0040] The polyether nitrile of the present invention preferably has a weight average molecular weight (Mw) in terms of polystyrene obtained by gel permeation chromatography (GPC) analysis and measurement, which is preferably 50,000 or more. If it is less than 40,000, the mechanical strength may sometimes deteriorate, so it is not preferred. In addition, the range of the weight average molecular weight (Mw) also makes moldability difficult, so it is more preferably in the range of 50,000 to 1,000,000, more preferably in the range of 50,000 to 500,000, and particularly preferably in the range of 50,000 to 300,000.

[0041] The polyether nitrile of the present invention preferably has a polystyrene-equivalent weight average molecular weight (Mw) and a number average molecular weight (Mn) measured by gel permeation chromatography (GPC) analysis, which satisfy the formula (i).

[0042] Formula (i): Mw / Mn≧2.4×10 -4 ×Mw-11.8 As described in the examples below, this relationship is the relationship between the measured values ​​of the weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the polyether nitrile, and the measured values ​​of the temperature (T) at the time of measuring the half-crystallization time and the half-crystallization time (τc1 / 2) at the temperature found by multivariate regression analysis. Therefore, it is understood by those skilled in the art of polyether nitrile related to the present invention that a polyether nitrile satisfying this relationship has a sufficient crystallization rate.

[0043] When the relationship of formula (i) is satisfied, the semi-crystallization time at 275°C is 100 seconds or less. Further, when the relationship of formula (ii) is satisfied, the semi-crystallization time at 275°C is 85 seconds or less, which is preferred. When the relationship of formula (iii) is satisfied, the semi-crystallization time at 275°C is 50 seconds or less, which is particularly preferred.

[0044] Formula (ii): Mw / Mn≧2.4×10 -4 ×Mw-11.4 Formula (iii): Mw / Mn≧2.4×10 -4 ×Mw-10.4 The repeating unit of the polyether nitrile of the present invention is not particularly limited, but is preferably a polyether nitrile having a repeating unit represented by the general formula (3). The repeating unit represented by the general formula (3) may have only one type of repeating unit or may have two or more types of repeating units. It is preferred to have only one type of repeating unit.

[0045] [Chemistry 11]

[0046] (In the formula, R represents a divalent group represented by general formula (1a) or general formula (1b), and r represents an integer of 1 to 4.) [Chemistry 12]

[0047] (Where R 1 Each independently represents a linear or branched alkyl group having 1 to 6 carbon atoms, a cyclic alkyl group having 5 or 6 carbon atoms, or a phenyl group, m each independently represents an integer of 0 to 4, n represents 0 or 1, p and q represent 0, 1 or 2, and * each represents a bonding position. [Chemistry 13]

[0048] (Where R 1 and m is the same as defined in the general formula (1a), Y represents an oxygen atom, a sulfur atom, a sulfonyl group, a carbonyl group, an alkylidene group having 1 to 15 carbon atoms, a fluorine-containing alkylidene group having 2 to 15 carbon atoms, a cycloalkylidene group having 5 to 15 carbon atoms, a phenylmethylidene group, a phenylethylidene group, a phenylene group or a fluorenylidene group, Z represents an oxygen atom, a sulfur atom or is unbridged, Ar each independently represents an aryl group having 6 to 8 carbon atoms, and * each represents a bonding position.) R in the general formula (1a) 1Each independently represents a straight-chain or branched alkyl group having 1 to 6 carbon atoms, a cyclic alkyl group having 5 or 6 carbon atoms, or a phenyl group, preferably a straight-chain or branched alkyl group having 1 to 4 carbon atoms, a cyclic alkyl group having 5 or 6 carbon atoms, or a phenyl group, more preferably a straight-chain or branched alkyl group having 1 to 4 carbon atoms, or a phenyl group, and particularly preferably an alkyl group having 1 carbon atom, i.e., a methyl group.

[0049] In the general formula (1a), m represents an integer of 0 to 4, preferably an integer of 0, 1 or 2, more preferably 0 or 1, and particularly preferably 0.

[0050] In the general formula (1a), n represents 0 or 1, and preferably 1.

[0051] In the general formula (1a), p and q each independently represent 0, 1 or 2, preferably 0 or 1, and particularly preferably 0.

[0052] When n is 1, and p and q are 0, the general formula (1a) can be expressed as the general formula (1a').

[0053] [Chemistry 14]

[0054] (Where R 1 , m and * are the same as those defined in the general formula (1a). The bonding positions in the general formula (1a') are preferably independently ortho or para to the direct bonding positions of the two benzene rings, and are particularly preferably both para. When m is 1 or 2, R 1 The bonding position of is preferably the meta position relative to the direct bonding position of the two benzene rings. 1 Preferred embodiments of m are the same as those in the general formula (1a).

[0055] When n, p and q are 0, the general formula (1a) is expressed as the general formula (1a")

[0056] [Chemistry 15]

[0057] (Where R 1 , m and * are the same as those defined in the general formula (1a). The bonding position in the general formula (1a") is preferably the para position or the meta position relative to another bonding position, and is particularly preferably the para position. 1 Preferred embodiments of m are the same as those in the general formula (1a).

[0058] In the general formula (1a), the general formula (1a') in which n is 1, p and q are 0, or the general formula (1a") in which n, p and q are all 0 is preferred.

[0059] R in the general formula (1b) 1and m are the same as defined in the general formula (1a), and preferred embodiments are also the same.

[0060] In the general formula (1b), Y represents an oxygen atom, a sulfur atom, a sulfonyl group, a carbonyl group, an alkylidene group having 1 to 15 carbon atoms, a fluorine-containing alkylidene group having 2 to 15 carbon atoms, a cyclic alkylidene group having 5 to 15 carbon atoms, a phenylmethylidene group, a phenylethylidene group, a phenylene group, or a fluorenylidene group, and the cyclic alkylidene group having 5 to 15 carbon atoms may contain an alkyl group as a branch. Specific examples of the cyclic alkylidene group include a cyclopentylidene group (having 5 carbon atoms), a cyclohexylidene group (having 6 carbon atoms), a 3-methylcyclohexylidene group (having 7 carbon atoms), a 4-methylcyclohexylidene group (having 7 carbon atoms), a 3,3,5-trimethylcyclohexylidene group (having 9 carbon atoms), a cycloheptylidene group (having 7 carbon atoms), and a cyclododecylidene group (having 12 carbon atoms).

[0061] In the general formula (1b), Y is preferably a sulfonyl group, a carbonyl group, an alkylidene group having 1 to 6 carbon atoms, a fluorine-containing alkylidene group having 2 to 6 carbon atoms, a cyclic alkylidene group having 5 to 12 carbon atoms, a phenylmethylene group, a phenylethylidene group, a phenylene group or a fluorenylidene group; more preferably a sulfonyl group, a carbonyl group, an alkylidene group having 1 to 3 carbon atoms, a fluorine-containing alkylidene group having 2 or 3 carbon atoms, a cyclic alkylidene group having 6 to 12 carbon atoms, a phenylmethylene group or a fluorenylidene group; further preferably an alkylidene group having 3 carbon atoms, i.e. a propylidene group, a fluorine-containing alkylidene group having 3 carbon atoms, i.e. a fluorine-containing propylidene group, a cyclic alkylidene group having 6 to 12 carbon atoms, or a fluorenylidene group; particularly preferably a 2,2′-isopropylidene group, a 2,2′-hexafluoroisopropylidene group, a cyclohexylidene group, a 3,3,5-trimethylcyclohexylidene group, a cyclododecylidene group and a fluorenylidene group.

[0062] Z in the general formula (1b) represents an oxygen atom, a sulfur atom, or has no bridge, preferably an oxygen atom or has no bridge, and more preferably has no bridge.

[0063] Ar in the general formula (1b) each independently represents an aryl group having 6 to 8 carbon atoms, and more preferably an aryl group having 6 carbon atoms.

[0064] R in the general formula (3) is preferably a divalent group represented by the general formula (1a), more preferably a divalent group represented by the general formula (1a') or a divalent group represented by the general formula (1a"), and particularly preferably at least one group selected from the divalent groups represented by the following structures.

[0065] [Chemistry 16]

[0066] In the general formula (3), r represents an integer of 1 to 4, preferably 1 or 2, and more preferably 1. When r is 1, the repeating unit represented by the general formula (3′) having ether bonds at both ortho positions of the cyano group is preferred.

[0067] [Chemistry 17]

[0068] (In the formula, R has the same definition as in general formula (3).) R in the general formula (3) is preferably a divalent group represented by the general formula (1a), more preferably a divalent group represented by the general formula (1a') or a divalent group represented by the general formula (1a"), and particularly preferably at least one group selected from the divalent groups represented by the following structures.

[0069] [Chemistry 18]

[0070] (In the formula, * represents each bonding position.) (Method for producing polyether nitrile of the present invention) The method for producing the polyether nitrile of the present invention includes a method of mixing two or more raw material polyether nitriles having different weight average molecular weights obtained in advance by polycondensation reaction (method 1) and a method of directly obtaining the polyether nitrile by polycondensation reaction (method 2).

[0071] Method 1 is preferred because the polycondensation reaction time for obtaining the raw material polyether nitrile used in the method is short and reasonable, and the method can be produced by a simple operation. In addition, if two or more raw material polyether nitrile having different weight average molecular weights are obtained by using the same aromatic dihydroxy compound (I) and the same dihalogenated benzonitrile compound (II), they can be mixed at the molecular level, so that the crystallization rate can be increased, and a molded product with high crystallinity and strongness can be obtained. Therefore, it is preferred, and more preferably, the raw material polyether nitrile has the same repeating unit in the repeating unit represented by the above general formula (3).

[0072] (Method 1) ・Production method of raw material polyether nitrile The raw material polyether nitrile used in the method 1 for producing polyether nitrile of the present invention can be obtained by subjecting an aromatic dihydroxy compound (I) and a dihalogenated benzonitrile compound (II) to a polycondensation reaction in the presence of a basic compound. The polyether nitrile having a repeating unit represented by the general formula (3) can be obtained, for example, by using a compound represented by the general formula (1) as the aromatic dihydroxy compound (I) and a compound represented by the general formula (2) as the dihalogenated benzonitrile compound (II) and subjecting them to a polycondensation reaction in the presence of a basic compound.

[0073] The reaction formula in this case is shown below.

[0074] [Chemistry 19]

[0075] (In the formula, R and r are the same as defined in the general formula (3), and X each independently represents a halogen atom.) Alternatively, a pre-synthesized alkali metal salt of an aromatic dihydroxy compound (I) and a dihalogenated benzonitrile compound (II) may be used to carry out a polycondensation reaction.

[0076] <Aromatic dihydroxy compound (I)> The aromatic dihydroxy compound (I) includes all aromatic compounds having two hydroxyl groups, and among them, the compound represented by the general formula (1) is preferred.

[0077] [Chemistry 20]

[0078] (In the formula, R has the same definition as in general formula (3).) The definition and preferred embodiment of R in the general formula (1) are the same as those in the general formula (3).

[0079] Specific examples of the aromatic dihydroxy compound (I) include hydroquinone, resorcinol, 2-phenylhydroquinone, 4,4'-biphenol, 3,3'-biphenol, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 1,1'-bi-2-naphthol, 2,2'-bi-1-naphthol, 1,3-bis[1-methyl-1-(4-hydroxyphenyl)ethyl]benzene, 1,4-bis[1-methyl-1-(4-hydroxyphenyl)ethyl]benzene, Benzene, 1,3-(4-hydroxybenzoylbenzene), 1,4-(4-hydroxybenzoylbenzene), 1,3-bis(4-hydroxyphenoxy)benzene, 1,4-bis(4-hydroxyphenoxy)benzene, 1,4-bis(4-hydroxyphenyl)benzene, 1,3-bis(4-hydroxyphenyl)benzene, 4,4'-isopropylidene biphenol (Bis-A), 2,2-bis(4-hydroxyphenyl)-1,1,1,3,3, 3-Hexafluoropropane, 4,4'-bishydroxybenzophenone, 4,4'-bishydroxydiphenyl sulfone, 4,4'-dihydroxydiphenyl ether, bis(4-hydroxyphenyl)methane, 9,9-bis(4-hydroxyphenyl)fluorene, 9,9-bis(3-phenyl-4-hydroxyphenyl)fluorene, 9,9-bis(3,5-diphenyl-4-hydroxyphenyl)fluorene, 9,9-bis(4-hydroxy-3-methylphenyl)fluorene, 9,9-bis(4-hydroxy- 3,5-dimethylphenyl)fluorene, 9,9-bis(4-hydroxy-3-cyclohexylphenyl)fluorene, 4,4'-isopropylidenebis(2-phenylphenol), bisphenol Z (1,1-bis(4-hydroxyphenyl)cyclohexane), bisphenol TMC (1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane), 1,1-bis(4-hydroxyphenyl)cyclododecane, 1,1-bis(4-hydroxyphenyl)-1-phenylethane, etc.

[0080] Among them, hydroquinone, resorcinol, and 4,4'-biphenol are preferred, and 4,4'-biphenol is particularly preferred.

[0081] <Dihalogenated benzonitrile compound (II)> The dihalogenated benzonitrile compound (II) includes all benzonitrile compounds having two halogen groups, and among them, the compound represented by the following general formula (2) is preferred.

[0082] [Chemistry 21]

[0083] (In the formula, r has the same definition as in the general formula (3), and X each independently represents a halogen atom.) X in the general formula (2) each independently represents a halogen atom, and each independently represents preferably a chlorine atom, a bromine atom or an iodine atom, more preferably each independently represents a chlorine atom or a bromine atom, and particularly preferably both represent chlorine atoms.

[0084] In the general formula (2), r represents an integer of 1 to 4, preferably 1 or 2, and more preferably 1. When r is 1, a structure represented by the general formula (2') in which a halogen atom is bonded to both ortho positions of a cyano group is preferred.

[0085] [Chemistry 22]

[0086] As the dihalogenated benzonitrile compound (II), specifically, for example, 2,6-difluorobenzonitrile, 2,5-difluorobenzonitrile, 2,4-difluorobenzonitrile, 2,6-dichlorobenzonitrile, 2,5-dichlorobenzonitrile, 2,4-dichlorobenzonitrile, 2,6-dibromobenzonitrile, 2,5-dibromobenzonitrile, 2,4-dibromobenzonitrile, 2,6-dinitrobenzonitrile, 2,5-dinitrobenzonitrile, 2,4-dinitrobenzonitrile, 1,4-dichloro-2,5-dicyanobenzene. In addition, reactive derivatives of these may also be used. Among these, 2,6-difluorobenzonitrile and 2,6-dichlorobenzonitrile are preferably used from the perspectives of reactivity and economy. These compounds may also be used in combination of two or more.

[0087] The reactive derivatives mentioned above, when taking the structure derived from 2,6-dihalogenobenzonitrile as an example, refer to compounds represented by the following general formula that can react with an aromatic dihydroxy compound. They refer to compounds derived from two 2,6-dihalogenobenzonitriles or from the reaction of 2,6-dihalogenobenzonitrile and an aromatic dihydroxy compound.

[0088] [Chemistry 23]

[0089] (In the formula, R has the same definition as in the general formula (3), and X has the same definition as in the general formula (2).) The molar ratio of the aromatic dihydroxy compound (I) to the dihalogenated benzonitrile compound (II) can be appropriately set depending on the target molecular weight, and is usually in the range of 0.5 to 2.0.

[0090] For example, when it is desired to obtain a polymer having a molecular weight in which the average number of repeating units in the general formula (3) exceeds 10, the molar ratio is preferably in the range of 0.9 to 1.1, more preferably in the range of 0.95 to 1.05, and particularly preferably in the range of 0.99 to 1.01. In order to maximize the polymerization rate of the polycondensation reaction, it is preferred to use the aromatic dihydroxy compound (I) and the dihalogenated benzonitrile compound (II) in a molar ratio of substantially 1.00.

[0091] On the other hand, when it is desired to obtain a low molecular weight polymer in which the average number of repeating units in the general formula (3) is 10 or less, the molar ratio is preferably in the range of 0.5 to 0.9 or in the range of 1.1 to 2.0.

[0092] Two or more kinds of the aromatic dihydroxy compound (I) and the dihalogenated benzonitrile compound (II) may be used in combination, but it is preferred to use only one kind of each compound from the viewpoint of increasing the crystallization rate, high crystallinity, and the toughness of the obtained molded article. When two or more kinds of the compounds are used, the molar ratio of the total amount of each of the aromatic dihydroxy compound (I) and the dihalogenated benzonitrile compound (II) is used as described above.

[0093] <Basic compounds> The alkaline compound may be any compound, whether organic or inorganic, as long as it can promote the desalting polycondensation reaction and does not affect the quality. An inorganic compound is preferred, among which an alkali metal compound or an alkaline earth metal compound is preferred, and an alkali metal compound is particularly preferred.

[0094] Examples of the organic base include tetramethylammonium hydroxide, triethylamine, N,N-diisopropylethylamine, 1,1,3,3-tetramethylguanidine (TMG), N,N-dimethyl-4-aminopyridine (DMAP), 2,6-lutidine, pyridine, 1,8-diazabicyclo[5.4.0]-7-undecene (DBU), 1,5-diazabicyclo[4.3.0]-5-nonene (DBN), 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene (M TBD), 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD), 1,8-bis(dimethylaminonaphthalene) (DMAN), 1,4-diazabicyclo[2.2.2]octane (DABCO), tert-butylimino-tris(pyrrolidine)phosphine, tert-butylimino-tris(dimethylamino)phosphine, 2-tert-butylimino-2-diethylamino-1,3-dimethylperhydro-1,3,2-diazaphosphine, tert-octylimino-tris(dimethylamino)phosphine, phosphazene base P 2 -Et, phosphazene base P 2 -t-Bu, phosphazene base P 3 -t-Bu, phosphazene base P 4 -t-Bu, phosphazene base P 4 -t-Oct.

[0095] Among the inorganic bases, examples of alkali metal compounds include alkali metals such as lithium, rubidium, cesium, potassium, and sodium; alkali metal hydrides such as lithium hydride, rubidium hydride, cesium hydride, potassium hydride, and sodium hydride; alkali metal hydroxides such as lithium hydroxide, rubidium hydroxide, cesium hydroxide, potassium hydroxide, and sodium hydroxide; alkali metal carbonates such as lithium carbonate, rubidium carbonate, cesium carbonate, potassium carbonate, and sodium carbonate; alkali metal bicarbonates such as lithium bicarbonate, rubidium bicarbonate, cesium bicarbonate, potassium bicarbonate, and sodium bicarbonate, etc. These may be used alone or in combination of two or more.

[0096] By using these alkali metal compounds, the specific surface area is 0.3 m 2 / g or more, the desalting polycondensation reaction can be carried out with high efficiency. The specific surface area of ​​the alkali metal compound is preferably 0.8 m 2 / g or more, more preferably 1.2m 2 By using an alkali metal compound with a larger specific surface area, the contact opportunity between the catalyst and the reaction raw materials can be further increased, so that the desalination polycondensation reaction can be carried out with higher efficiency. The specific surface area is less than 0.3m 2 / g, the desalting polycondensation reaction cannot be performed with sufficiently high efficiency unless the amount of the catalyst is increased. However, increasing the amount of the catalyst is not preferred because it affects the quality of the polycondensate.

[0097] From the above, as the basic compound in the production method of the present invention, preferably, lithium carbonate, rubidium carbonate, cesium carbonate, potassium carbonate and sodium carbonate and other alkali metal carbonates, lithium carbonate, potassium carbonate and sodium carbonate are more preferred, especially from the perspective of availability, preferably a specific surface area of ​​0.3m 2 / g or more of potassium carbonate and sodium carbonate.

[0098] In the polycondensation reaction for obtaining the raw material polyether nitrile, the amount of the basic compound used is preferably, for example, 2 mole times or more in the case of an alkali metal compound, based on the alkali metal ions contained, relative to the aromatic dihydroxy compound (I). However, if used in too large an amount, a side reaction such as cleavage of ether bonds may occur during the polycondensation. Therefore, it is preferably used in the range of 2 to 4 mole times, more preferably in the range of 2 to 2.4 mole times, and particularly preferably in the range of 2 to 2.2 mole times.

[0099] Furthermore, in order to maximize the polymerization rate of the polycondensation reaction, when the aromatic dihydroxy compound (I) and the dihalogenated benzonitrile compound (II) are used in a substantially molar ratio of 1.00, if the alkali metal ion is used in an amount within a range of 2 to 1 molar times relative to the aromatic dihydroxy compound (I), it is possible to produce a polyether nitrile having a molecular weight ranging from infinity to 1 in the average number of units of the general formula (3).

[0100] <Reaction solvent> A reaction solvent may be used in the polycondensation reaction for obtaining the raw material polyether nitrile, and an aprotic solvent is preferably used as the reaction solvent.

[0101] As aprotic solvents, specifically, N,N-dimethylacetamide, N,N-dimethylformamide, N-methyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, γ-butyrolactone, sulfolane, dimethyl sulfoxide, diethyl sulfoxide, dimethyl sulfone, diethyl sulfone, diisopropyl sulfone, diphenyl sulfone, diphenyl ether, benzophenone, dialkoxybenzene (the number of carbon atoms in the alkoxy group is 1 to 4), trialkoxybenzene (the number of carbon atoms in the alkoxy group is 1 to 4), etc. can be listed. Among these solvents, polar organic solvents with high dielectric constants such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, sulfolane, diphenyl sulfone, and dimethyl sulfoxide are particularly suitable. These can be used alone or in combination of two or more.

[0102] The amount of the aprotic solvent used is not particularly limited as long as it is an amount that allows good stirring and dispersion of the alkali metal salt, except that the raw materials can be uniformly dissolved. The amount that maximizes the volumetric efficiency of the polycondensation reactor can be selected relative to the raw materials and target polymer used. It is usually selected within the range of 0.5 to 20 times the total weight of the raw materials and the alkali metal salt.

[0103] <Polycondensation reaction method> The polycondensation reaction for obtaining the raw material polyether nitrile may be divided into an oligomer formation step (A) and a polymerization step (B) and carried out by changing the respective reaction methods, or may be carried out without particularly distinguishing the steps.

[0104] The oligomer forming step (A) is a step of forming an oligomer by polycondensing the aromatic dihydroxy compound (I) and the dihalogenated benzonitrile compound (II) in the presence of a basic compound. The oligomer referred to herein is not particularly limited, and generally refers to a polycondensation reaction product having a polymer reduced viscosity of less than 1.

[0105] The polymer forming step (B) is a step of further subjecting the oligomer obtained in step (A) to a polycondensation reaction to form a polymer. In this case, the oligomer may be directly used as the polycondensation reaction liquid of step (A), or may be used as an oligomer obtained by performing step (A) separately and isolating the oligomer.

[0106] The polycondensation reaction for obtaining the polyether nitrile of the present invention includes an operation of discharging the water generated during the desalination reaction to the outside of the system. As an operation method, for example, a method of performing a reaction at a temperature at which a desalination reaction can proceed in the presence of a solvent that forms an azeotrope with water, and distilling water from the reaction mixture by using the solvent that forms an azeotrope with water during the reaction. In this way, the reaction can be maintained in a substantially anhydrous state.

[0107] The temperature at which the desalting reaction starts varies depending on the raw materials, but is generally about 130° C. For example, when 4,4'-biphenol is used as the aromatic dihydroxy compound (I), 2,6-dichlorobenzonitrile is used as the dihalogenated benzonitrile compound (II), potassium carbonate is used, sulfolane (boiling point 285° C.) is used as the aprotic solvent, and toluene is used as the solvent that forms an azeotrope with water, the reaction temperature is preferably in the range of 130 to 170° C.

[0108] Specific examples of the solvent that forms an azeotrope with water include aromatic hydrocarbons such as benzene, toluene, xylene, hexane, cyclohexane, octane, chlorobenzene, dioxane, tetrahydrofuran, anisole, and phenetole. These may be used alone or in combination of two or more.

[0109] When a solvent that forms an azeotrope with water is used, the solvent that forms an azeotrope with water is preferably used in an amount within a range of 1 to 100 parts by weight relative to 100 parts by weight of the aprotic solvent, more preferably within a range of 1 to 10 parts by weight, and further preferably within a range of 2 to 5 parts by weight from the viewpoint of volumetric efficiency or solvent recovery.

[0110] When the reaction is continued, it is preferred to remove the water generated by the reaction while maintaining the reaction system in a substantially anhydrous state. When the generated water is not removed sufficiently, it reacts with the dihalogenated benzonitrile compound composition (II) to form a byproduct of a phenol skeleton, thereby only generating a low molecular weight product. That is, in order to obtain a high molecular weight polyether nitrile, the reaction system is preferably substantially anhydrous, and more preferably less than 0.5% by weight.

[0111] <Polycondensation reaction conditions> The reaction temperature of the polycondensation reaction for obtaining the raw material polyether nitrile is in the range of 140 to 300° C. Within this range, the reaction can be continued at a constant temperature, and the temperature may be increased as the polycondensation reaction proceeds.

[0112] When the polycondensation reaction is carried out by dividing the steps into an oligomer formation step (A) and a polymerization step (B), the temperature of the oligomer formation step (A) is preferably in the range of 140 to 200° C., more preferably in the range of 150 to 170° C., further preferably in the range of 155 to 165° C., and the polymerization step (B) is preferably in the range of 200 to 300° C., more preferably in the range of 210 to 270° C., further preferably in the range of 210 to 240° C., particularly preferably in the range of 215 to 230° C.

[0113] For example, when 4,4'-biphenol is used as the aromatic dihydroxy compound (I), 2,6-dichlorobenzonitrile is used as the dihalogenated benzonitrile compound (II), potassium carbonate is used, sulfolane (boiling point 285°C) is used as the aprotic solvent, and toluene is used as the solvent that forms an azeotrope with water, the reaction temperature is preferably in the range of 190 to 280°C.

[0114] The pressure may be normal pressure, higher pressure or lower pressure.

[0115] The polycondensation reaction is preferably carried out under an inert gas atmosphere, for example, under a nitrogen atmosphere, at atmospheric pressure.

[0116] The reaction time of the polycondensation reaction for obtaining the raw material polyether nitrile varies depending on the molar ratio of the aromatic dihydroxy compound (I) to the dihalogenated benzonitrile compound (II) or the amount of the basic compound used, and can be arbitrarily set according to the target molecular weight of the polyether nitrile, but is usually 3 to 20 hours.

[0117] <Post-reaction treatment> The polycondensation reaction product after the polycondensation reaction to obtain the raw material polyether nitrile can be used directly as the raw material polyether nitrile, but it is preferred to perform a post-reaction treatment. The polycondensation reaction product can be extracted from the reactor, pulverized after cooling and solidification, and then subjected to the subsequent steps of the washing step, drying step, and the step of producing the molding material (pellets, chips), or the polycondensation reaction product extracted from the reactor can be directly put into the washing tank of the washing step, or the solvent used in the washing step described later can be injected into the reactor after the polycondensation reaction is completed, and transferred to the washing step in a slurry state or a wax state.

[0118] The washing step is a step of washing for removing salts, reaction solvents, and the like contained in the polycondensation reaction product obtained by the polycondensation reaction.

[0119] The washing step can be performed by a known method using a solvent such as alcohol, ketone, aromatic hydrocarbon, aliphatic hydrocarbon, water, etc. to extract and wash the reaction solvent in the polycondensation reaction product, and then preferably washing with water to remove the salt generated by the desalting reaction in the polycondensation reaction product.

[0120] As a specific operation, the polycondensation reaction product in a crushed, slurry or wax state can be transferred to a container equipped with a stirrer, and the operations of stirring, washing and filtering with a washing solvent can be repeated until the reaction solvent or salt content becomes below the target content.

[0121] As for the apparatus, in addition to the cleaning tank and the pressure filter or the centrifugal separator, a multifunctional filtering apparatus that can perform cleaning, filtering, and drying in one apparatus may be used.

[0122] Specific examples of the extraction and washing solvent other than water as the reaction solvent include, for example, methanol, ethanol, propanol, isopropanol, butanol, isobutanol, sec-butanol, tert-butanol, n-pentanol, isopentanol, tert-pentanol, n-hexanol, cyclohexanol, n-octanol, octanol, etc. Specific examples of alcohols include, for example, acetone, methyl ethyl ketone, methyl n-propyl ketone, diethyl ketone, 2-hexanone, 3-hexanone, methyl tert-butyl ketone, di-n-propyl ketone, diisopropyl ketone, diisobutyl ketone, di-n-pentyl ketone, diacetyl, acetylacetone, cyclohexanone, benzophenone, etc. Examples of aliphatic hydrocarbons include saturated aliphatic hydrocarbons such as n-hexane, 2-methylheptane, 3-methylheptane, 2,2-dimethylbutane, 2,3-dimethylbutane, n-heptane, 2-methylhexane, 3-methylhexane, 2,2-dimethylpentane, 2,3-dimethylpentane, 2,4-dimethylpentane, 3,3-dimethylpentane, 3-ethylpentane, 2,2,3-trimethylbutane, and cyclohexane, and unsaturated hydrocarbons such as 1-hexene, 1-heptene, 1-octene, and cyclohexene. Examples of aromatic hydrocarbons include benzene, toluene, o-xylene, m-xylene, p-xylene, ethylbenzene, n-propylbenzene, isopropylbenzene, n-butylbenzene, tert-butylbenzene, styrene, and allylbenzene.

[0123] Among these, methanol, ethanol, acetone, methyl ethyl ketone, xylene, toluene and the like are preferred. In view of the operability and the ease of distillation recovery of the reaction solvent after washing, acetone or methanol is preferred.

[0124] For washing the alkali metal salt such as potassium chloride generated in the desalting polycondensation reaction, water is preferably used, but acidic water containing oxalic acid or acetic acid at a low concentration may also be used.

[0125] The conditions of the washing step may be appropriately selected in terms of the amount of washing solvent used, the number of washing times, and the washing temperature, depending on the amount of the residual reaction solvent or the residual alkali metal salt to be removed.

[0126] The drying step is a step of drying the polycondensation reaction product obtained by the washing step.

[0127] The polycondensation reaction product containing water after washing can be dried by a known method. As a dryer, a known device such as an evaporator, a plate oven, a drum dryer, etc. can be used.

[0128] The target water content is usually 0.5% by weight or less, preferably 0.4% by weight or less, and more preferably 0.3% by weight or less.

[0129] The drying process can be carried out under any conditions as long as the temperature is below the melting point of the polycondensation reaction product and the moisture can be removed. It is preferably carried out under reduced pressure in an inert gas (nitrogen, argon, etc.) environment or in an inert gas flow in a manner that minimizes contact with air. The dried polycondensation reaction product is basically a powder.

[0130] The raw material polyether nitrile may be in the form of a molding material (granules, chips, etc.) for producing a molded product of polyether nitrile. There is no particular limitation on the method for producing the molding material, and the raw material polyether nitrile obtained by heating and melting the powder and forming it into the shape of a molding material such as granules and chips. The heating, melting and molding operations are preferably performed under oxygen blocking or in an inert gas environment such as nitrogen.

[0131] Generally, when manufacturing forming materials such as pellets or chips, a single-axis, double-axis or multi-axis extruder, Banbury mixer, kneader, rolling mill or other melt kneading device can be used, or a compression molding machine can be used to cut the produced sheet to manufacture forming materials such as pellets or chips.

[0132] When manufacturing molding materials, the industrially preferred process is as follows. The polyether nitrile powder that has been polycondensed, crushed, washed, and vacuum dried is directly transferred and stored in a silo sealed with nitrogen or the like without being exposed to the outside air. When formed into a shape of pellets or chips, it is directly transferred to an extruder through a pipe together with nitrogen. In addition, melt kneading is performed without contact with oxygen (air), and the molten polymer from the mold is cut in water or the wire is water-cooled and cut to granulate.

[0133] As the conditions of the manufacturing process of the molding material (pellets, fragments), in terms of melt processing conditions, the above operation is carried out at a temperature at which the polymer is fully melted. The upper limit of the temperature during melt processing is carried out below 500°C. The raw material polyether nitrile obtained by using biphenol and 2,6-dichlorobenzonitrile used in the example has a melting point of about 345°C, so it is suitable for processing at a temperature higher than 360°C. The upper limit of the temperature is preferably below 480°C, more preferably below 450°C, further preferably below 430°C, and particularly preferably below 400°C.

[0134] ・Blending of raw material polyether nitrile According to the above method, two or more raw material polyether nitriles having different weight average molecular weights are prepared respectively, and appropriate amounts of the various raw material polyether nitriles are mixed so as to obtain the polyether nitrile of the present invention. More specifically, in view of the Mw and Mn of the various raw material polyether nitriles, appropriate amounts are mixed so as to obtain the desired Mw and Mn of the polyether nitrile of the present invention.

[0135] When producing a polyether nitrile having a half crystallization time of 100 seconds or less at 275°C, it is preferred to mix the raw polyether nitrile in a manner that satisfies the relationship of formula (i). When producing a polyether nitrile having a half crystallization time of 85 seconds or less at 275°C, it is more preferred to mix the raw polyether nitrile in a manner that satisfies the relationship of formula (ii). When producing a polyether nitrile having a half crystallization time of 50 seconds or less at 275°C, it is particularly preferred to mix the raw polyether nitrile in a manner that satisfies the relationship of formula (iii).

[0136] Furthermore, the polyether nitrile of the present invention may be used as one of the raw material polyether nitrile to be mixed, and the polyether nitrile of the present invention may be produced by shortening or lengthening the semi-crystallization time of the polyether nitrile to be used in order to achieve a desired molding cycle.

[0137] The form of the raw material polyether nitrile to be mixed is not particularly limited, and specifically, for example, the form of a polycondensation reaction product after the polycondensation reaction of the raw material polyether nitrile is completed, a washed product of the polycondensation reaction product, a powder, and a molding material (granules, chips, etc.) are listed. Among them, the form in the shape of a powder or a molding material (granules, chips, etc.) is preferred, and the powder is particularly preferred.

[0138] The form of the two or more raw material polyether nitriles having different weight average molecular weights to be mixed is not particularly limited, and examples thereof include the form of all polycondensation reactants, all powders, all molding materials, the form of polycondensation reactants and powders, the form of polycondensation reactants and molding materials, the form of powders and molding materials, etc. Among them, the form of all powders, all molding materials, or the form of powders and molding materials is preferred, and the form of all powders is more preferred.

[0139] When all the powders are mixed, when all the powders are mixed in the form of molding materials, or when the powders and molding materials are mixed in the form of powders, the mixture may be mixed without melting, or may be mixed after heating and melting. In the case of heating and melting, the mixture may be directly provided to the step of preparing the molding material described later.

[0140] When the polycondensation reaction product and the washing product of the polycondensation reaction product are mixed, it is preferred that after the polyether nitrile of the present invention is obtained by the mixing, the polyether nitrile is treated according to the above-mentioned post-reaction treatment method to remove salts or reaction solvents contained in the polycondensation reaction product, or to remove the contained water. By such treatment, the powder of the polyether nitrile of the present invention can be obtained.

[0141] In order to obtain a polyether nitrile having excellent melt fluidity, the mixing operation is preferably performed under oxygen blocking or in an inert gas atmosphere such as nitrogen.

[0142] (Method 2) In the case of the method of directly obtaining the polyether nitrile of the present invention by polycondensation reaction (method 2), the polyether nitrile can be obtained by subjecting an aromatic dihydroxy compound (I) and a dihalogenated benzonitrile compound (II) to polycondensation reaction in the presence of a basic compound, similarly to the method of producing the raw material polyether nitrile.

[0143] The types of the aromatic dihydroxy compound (I), dihalogenated benzonitrile compound (II) and basic compound that can be used in the polycondensation reaction, the type and amount of the reaction solvent, the method of the polycondensation reaction and the conditions of the polycondensation reaction are the same as those for the polycondensation reaction of the above-mentioned raw material polyether nitrile.

[0144] The aromatic dihydroxy compound (I) and the dihalogenated benzonitrile compound (II) may be used in combination of two or more compounds, but it is preferred to use only one compound from the viewpoint of increasing the crystallization rate, high crystallinity, and the durability of the obtained molded article. When two or more compounds are used, the total molar ratio of the aromatic dihydroxy compound (I) and the dihalogenated benzonitrile compound (II) is used as described above.

[0145] The molar ratio of the aromatic dihydroxy compound (I) to the dihalogenated benzonitrile compound (II) is substantially 1.00. When the basic compound is, for example, an alkali metal compound, the polycondensation reaction is carried out using 1 mole or more of the basic compound based on the alkali metal ions contained in the aromatic dihydroxy compound (I).

[0146] The time of the polycondensation reaction can be obtained by allowing the polycondensation reaction to proceed until the reduced viscosity of the polyether nitrile increases to a maximum value, and then continuing the reaction in a region where the reduced viscosity begins to decrease until the polyether nitrile of the present invention is obtained. Specifically, it varies depending on the amount of the basic compound used, the reaction temperature, and other conditions, but the polyether nitrile of the present invention can be obtained by continuing the reaction for 15 to 50 hours, preferably 20 to 50 hours.

[0147] <Post-reaction treatment> The polycondensation reaction product after the polycondensation reaction for obtaining the polyether nitrile of the present invention is extracted from the reactor, and after being cooled and solidified, it is pulverized and then subjected to the subsequent steps of a washing step, a drying step, and a step of producing a molding material (pellets, chips). Alternatively, the polycondensation reaction product extracted from the reactor is directly put into a washing tank of a washing step. Alternatively, a solvent used in the washing step described later is injected into the reactor after the polycondensation reaction is completed, and the product is transferred to the washing step in a slurry state or a wax state.

[0148] The washing step and drying step applied to the polycondensation reaction product after the polycondensation reaction to obtain the polyether nitrile of the present invention can be carried out in the same manner as the washing step and drying step applied to the polycondensation reaction product after the polycondensation reaction to obtain the raw material polyether nitrile.

[0149] (Molding material of polyether nitrile of the present invention) The polyether nitrile of the present invention obtained by the above method 1 or method 2 can be formed into a shape of a molding material (granules, chips, etc.) for manufacturing a molded product. There is no particular limitation on the method for manufacturing the molding material. The polyether nitrile of the present invention obtained as described above can be heated and melted to form the shape of a molding material such as granules, chips, etc. The heating, melting and molding operations are preferably performed under oxygen blocking or in an inert gas environment such as nitrogen.

[0150] Generally, when manufacturing forming materials such as pellets or chips, a single-axis, double-axis or multi-axis extruder, Banbury mixer, kneader, rolling mill or other melt kneading device can be used, or a compression molding machine can be used to cut the produced sheet to manufacture forming materials such as pellets or chips.

[0151] When manufacturing molding materials, the industrially preferred process is as follows. The polyether nitrile powder that has been polycondensed, crushed, washed, and vacuum dried is directly transferred and stored in a silo sealed with nitrogen or the like without being exposed to the outside air. When formed into a shape such as pellets or fragments, it is directly transferred to an extruder through a pipe together with nitrogen. In addition, melt kneading is performed without contact with oxygen (air), and the molten polymer from the mold is cut in water or the wire is water-cooled and cut to granulate.

[0152] As the conditions for the manufacturing process of the molding material (granules, fragments), the above operation is carried out at a temperature at which the polymer is fully melted, with respect to the melt processing conditions. The upper limit of the temperature during the melt processing is carried out below 500°C. The polyether nitrile powder obtained by using the biphenol used in the embodiment has a melting point of about 345°C, so it is suitable for processing at a temperature higher than 360°C, and the upper limit of the temperature is preferably carried out below 480°C, more preferably below 450°C, further preferably below 430°C, and particularly preferably below 400°C.

[0153] (Polyether nitrile resin composition of the present invention) The polyether nitrile of the present invention can be mixed with at least one selected from the group consisting of a thermoplastic resin material (A), an additive (B), and a filler (C) to prepare a polyether nitrile resin composition. The polyether nitrile of the present invention used here is preferably the polyether nitrile obtained by method 1.

[0154] Specific examples of the thermoplastic resin material (A) contained in the polyether nitrile resin composition include high-density polyethylene, medium-density polyethylene, isotactic polypropylene, acrylonitrile-butadiene-styrene (ABS) resin, acrylonitrile-styrene (AS) resin, acrylic resin, fluororesin (polytetrafluoroethylene, etc.), polyester, polycarbonate, polyarylate, aliphatic polyamide, aromatic polyamide, polysulfone, polyether sulfone, polyether ketone, polyether ether ketone, polyphenylene sulfide, polyether imide, polyamide-imide, polyester imide, and modified polyphenylene ether.

[0155] Specific examples of the additive (B) contained in the polyether nitrile resin composition include hydrophilic agents, antioxidants, secondary antioxidants, flame retardants, flame retardant aids, plasticizers, lubricants, mold release agents, antifogging agents, weathering stabilizers, light stabilizers, hydrolysis resistance improvers, fluidity improvers, ultraviolet absorbers, antistatic agents, metal deactivators, near infrared absorbers, and colorants (dyes, pigments).

[0156] Specific examples of the filler (C) contained in the polyether nitrile resin composition include various metal powders, powders of inorganic acid metal salts (calcium carbonate, zinc borate, calcium borate, zinc stannate, calcium sulfate, barium sulfate, etc.), powders of metal oxides (magnesium oxide, iron oxide, titanium oxide, zinc oxide, aluminum oxide, etc.), powders of metal hydroxides (aluminum hydroxide, magnesium hydroxide, zirconium hydroxide, aluminum oxide hydrate (boehmite), etc.), powders of metal sulfides (zinc sulfide, molybdenum sulfide, tungsten sulfide, etc.), and ceramic materials such as silver nanowires, carbon fibers, glass fibers, carbon nanotubes, graphene, and silica.

[0157] These (A) to (C) can be blended in appropriate amounts depending on the intended use, but the total amount of (A) to (C) blended is preferably 90% by weight or less based on the total weight of the polyether nitrile resin composition.

[0158] (Method for producing the polyether nitrile resin composition of the present invention) The method for producing the polyether nitrile resin composition of the present invention is a method of mixing the polyether nitrile of the present invention with at least one selected from a thermoplastic resin material (A), an additive (B), and a filler (C). In this case, the polyether nitrile is preferably in the form of a powder or a molding material.

[0159] In this mixing method, when the polyether nitrile of the present invention produced by method 1 is used, two or more raw material polyether nitrile having different weight average molecular weights are mixed with at least one of (A) to (C) selected from the group consisting of a thermoplastic resin material (A), an additive (B), and a filler (C), wherein the two or more raw material polyether nitrile, when mixed, will produce the polyether nitrile of the present invention.

[0160] The step of mixing the components at this time preferably includes the following steps: first, a "polyether nitrile mixing step" of mixing two or more raw material polyether nitrile having different weight average molecular weights by the above-mentioned method to obtain the polyether nitrile of the present invention, and then a "resin composition component mixing step" of mixing the polyether nitrile obtained in the "polyether nitrile mixing step" with at least one of (A) to (C) selected from the group consisting of a thermoplastic resin material (A), an additive (B), and a filler (C).

[0161] When the polyether nitrile of the present invention produced by method 2 is used, the powder or molding material of the polyether nitrile is mixed with at least one selected from the group consisting of (A) to (C) of a thermoplastic resin material (A), an additive (B), and a filler (C).

[0162] The polyether nitrile resin composition of the present invention thus obtained can be used to prepare a molding material of the polyether nitrile resin composition in the same manner as in the process of preparing a molding material. In order to obtain a polyether nitrile resin composition molding material having excellent melt fluidity, melt molding in the process of preparing the molding material is preferably performed under oxygen blocking or in an inert gas environment.

[0163] The polyether nitrile obtained by the method of the present invention can be made into a molding material by the above method, and can also be used for the production of molded products or parts using the material, and has heat resistance, chemical resistance, flame retardancy, and high mechanical properties. For example, it can be used for electrical / electronic applications such as personal computers and semiconductor parts, automotive applications such as gears or bearings, housings around engines, medical equipment, and applications in the aerospace field.

[0164] Example The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0165] The analysis method in the present invention is as follows.

[0166] (1) Semi-crystallization time The half crystallization time, which is the time required to reach half of the total heat of crystallization at the measurement temperature, was measured for the polyether nitrile pellets obtained in the Examples and Comparative Examples described below using an input compensation differential scanning calorimeter (DSC8500 manufactured by PerkinElmer) under the following conditions.

[0167] <Conditions> Sample: 5mg Measurement environment: Nitrogen Temperature control: Raise the temperature from 30°C to 370°C at a heating rate of 500°C / min, hold for 3 minutes, then cool to the measurement temperature at a cooling rate of 500°C / min and hold at the measurement temperature.

[0168] (2) Determination of molecular weight The weight average molecular weight (Mw) and number average molecular weight (Mn) of the obtained polyether nitrile were measured using the following apparatus and conditions on a solution obtained by diluting a 1% p-chlorophenol solution of the polyether nitrile 10 times with chloroform. The molecular weight distribution Mw / Mn was determined from these values.

[0169] Equipment: Gel permeation chromatography: 515HPLC pump, 717plus automatic injection device, 2487 UV-visible detector (manufactured by Waters Co., Ltd., Japan) Chromatographic column: 2×PLgel5μMIXED-D, 7.5×300mm (Agilent Technology) Column temperature: 40°C Flow rate: 1.0mL / min Injection volume: 2.5 μL Detection: UV-Vis detector: 254nm Column calibration: Monodisperse polystyrene (EasiCal PS-1 Agilent Technology) Molecular weight calibration: relative calibration method (polystyrene conversion) Analysis software: Empower3 (manufactured by Japan Waters Co., Ltd.) (3) Reduced viscosity η of polymer red (dL / g) determination method 0.1 g of the sample was dissolved in about 5 g of p-chlorophenol at 180°C, transferred to a 10 mL volumetric flask and filled to the mark at 40°C. The volume was fixed with a 5 mL full-volume pipette and placed in an Ostwald viscometer (capillary 0.75 mm). The viscometer was then placed in a constant temperature bath at 40.0°C for 15 minutes, and the flow time T was measured and calculated using the following formula.

[0170] [Calculation formula] Reduced viscosity η red ={(T / T 0 )-1} / C C: concentration of the solution (g / dL) T: Flow time of sample solution (seconds) T 0 : Flow time of parachlorophenol (seconds) (4) Analysis of thermal properties: melting point (Tm), glass transition temperature (Tg), cooling crystallization temperature (Tc) Thermal properties were measured using a differential scanning calorimeter (DSC-60, manufactured by Shimadzu Corporation) under the following conditions using pellets of polyether nitrile obtained in the examples and comparative examples described below. The melting point (Tm) and glass transition temperature (Tg) were measured during temperature increase, and the temperature drop crystallization temperature was measured after holding at 370°C for 1 minute and then dropping the temperature at 10°C per minute.

[0171] <Conditions> Sample: 10mg Nitrogen flow rate: 50mL / min. Temperature range: 50~370℃ Temperature change speed: 10℃ / min. <Synthesis example 1> Into a 3-liter four-mouth reaction vessel equipped with a mechanical stirrer, a thermometer, a dry nitrogen inlet and a reflux, 298.45 g (1.735 moles) of 2,6-dichlorobenzonitrile (hereinafter referred to as "DCBN"), 323.08 g (1.735 moles) of 4,4'-biphenol (hereinafter referred to as "BP"), 251.79 g (1.822 moles: 1.05 moles relative to BP), 60 g of toluene and 1562 g of anhydrous sulfolane were placed. The mixture was heated from room temperature in a nitrogen stream, and heated to 160°C while stirring at 250 rpm. At 130°C or above, carbon dioxide was generated by the reaction of potassium carbonate and "BP". After 3 hours at 160°C, the oligomerization reaction of "DCBN" and "BP" was completed. Then, by switching the cooling water of the reflux device to warm water and removing water and toluene from the outlet, the temperature was raised to 220°C and a polycondensation reaction was performed for 1.5 hours.

[0172] After the polycondensation reaction, the polycondensation reaction product was extracted from the bottom of the reaction container and allowed to cool to solidify. The solid product was crushed with a Waring mixer, washed with acetone and distilled water, and dried in a vacuum oven at 120° C. for 16 hours to obtain 470 g of a powdered raw material polyether nitrile (hereinafter referred to as “raw material resin A”) (yield 95%).

[0173] The raw material polyether nitrile obtained by the polycondensation reaction of "DCBN" and "BP" has a repeating unit represented by the following formula.

[0174] [Chemistry 24]

[0175] <Synthesis example 2> In Synthesis Example 1, a raw material polyether nitrile (hereinafter referred to as "raw material resin B") was obtained in the same manner as in Synthesis Example 1 except that the polycondensation reaction was carried out at a temperature of 220° C. for 8.0 hours.

[0176] <Synthesis Example 3> In Synthesis Example 1, a raw material polyether nitrile (hereinafter referred to as "raw material resin C") was obtained in the same manner as in Synthesis Example 1 except that the polycondensation reaction was carried out at a temperature of 220° C. for 1.0 hour.

[0177] <Synthesis example 4> In Synthesis Example 1, a raw material polyether nitrile (hereinafter referred to as "raw material resin D") was obtained in the same manner as in Synthesis Example 1 except that the polycondensation reaction was carried out at a temperature of 220° C. for 3.0 hours.

[0178] <Synthesis Example 5> In Synthesis Example 1, except that the amount of anhydrous potassium carbonate was changed to 237.42 g (1.718 mol: 0.90 mol times relative to BP) and the reaction was carried out at 220° C. for 1 hour, a raw material polyether nitrile (hereinafter referred to as “raw material resin E”) in powder form was obtained by the same operation as Synthesis Example 1.

[0179] The weight average molecular weight (Mw), number average molecular weight (Mn), and reduced viscosity η of the raw material polyether nitrile (raw material resin A to E) obtained in Synthesis Examples 1 to 5 were analyzed by the above-mentioned analysis method. red The results are shown in Table 1 together with the "Mw / Mn" value.

[0180] [Table 1]

[0181] <Examples 1 to 3, Comparative Examples 1 to 5> The raw material polyether nitrile (raw material resins A to E) obtained in the above Synthesis Examples 1 to 5 were mixed into powders according to the resin types and their weight ratios in the columns of raw material resin (1) and raw material resin (2) in Table 2 below, and melt-kneaded at 380° C. under nitrogen. Then, pellets were prepared.

[0182] The weight average molecular weight (Mw), number average molecular weight (Mn), thermal properties, and crystallization half times at 275° C. and 300° C. of the obtained polyether nitrile were measured by the above-mentioned methods.

[0183] The results are shown in Table 2.

[0184] [Table 2]

[0185] As shown in Table 2, it can be seen that the semi-crystallization time of the polyether nitriles of Examples 1 to 3 of the present invention at 275° C. is 100 seconds or less, which is shorter than the semi-crystallization time of the polyether nitriles of the conventional Comparative Examples 1 to 5. Even when compared with polyether nitriles having similar weight average molecular weights (Comparative Example 1 and Examples 1 and 2, Comparative Example 2 and Example 3), the semi-crystallization time is greatly shortened, and the crystallization rate is greatly improved.

[0186] Furthermore, it is also clear that the polyether nitrile of the present invention can also maintain a high melting point (Tm) and a high glass transition temperature (Tg).

[0187] Therefore, since the polyether nitrile of the present invention has a high crystallization rate, a molded product of polyether nitrile having high heat resistance can be obtained in a short molding cycle, which is very useful.

[0188] It was further clarified that the polyether nitrile of Examples 1 to 3 of the present invention had a high weight average molecular weight of 50,000 or more and had very excellent mechanical properties.

[0189] <Relationship between half crystallization time (τc1 / 2: seconds) and weight average molecular weight (Mw), molecular weight distribution (Mw / Mn), and temperature (T: °C)> For the polyether nitriles obtained in Examples 1 to 3 and Comparative Examples 1 and 3 to 5, the measured weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn), the temperature (T) at which the half-crystallization time is measured, and the half-crystallization time (τc1 / 2) measured at the same temperature, the relationship between the half-crystallization time (τc1 / 2) and the weight average molecular weight (Mw), molecular weight distribution (Mw / Mn), and temperature (T) was analyzed by multiple regression analysis using Microsoft Excel, and the corrected R 2 The analysis result was obtained with a high accuracy of 0.94, and the relationship of formula (I) was found. The above-mentioned measured values ​​used for the multiple regression analysis are shown in Table 3, and the multiple regression analysis results are shown in Table 4.

[0190] Formula (I): τc1 / 2=0.00873×Mw-36.4×Mw / Mn+1.02×T-609.8 [Table 3]

[0191] [Table 4]

[0192] As can be seen from formula (I), the relationship between the molecular weight distribution (Mw / Mn) and the weight average molecular weight (Mw) of polyether nitrile having a crystallization half time of 100 seconds or less at a temperature of 275° C. can be expressed by the following formula (i).

[0193] Formula (i): Mw / Mn≧2.4×10 -4 ×Mw-11.8 That is, it can be seen that in the relationship between the molecular weight distribution (Mw / Mn) and the weight average molecular weight (Mw), there is a relationship corresponding to Mw / Mn=2.4×10 -4 The molecular weight distribution (Mw / Mn) and the weight average molecular weight (Mw) of the polyether nitrile in the region above the straight line of ×Mw-11.8 have a crystallization half time of 100 seconds or less at a temperature of 275°C.

[0194] The relationship between the molecular weight distribution (Mw / Mn) and the weight average molecular weight (Mw) is shown in the graph of "Mw is in the range of 50,000 to 80,000, and Mw / Mn is in the range of 1 to 10". Figure 1 The molecular weight distribution (Mw / Mn) and weight average molecular weight (Mw) of polyether nitrile are in a straight line: "Mw / Mn = 2.4 × 10 -4In the upper oblique line shaded area of ​​×Mw-11.8", the half crystallization time at a temperature of 275°C is 100 seconds or less.

[0195] Furthermore, from formula (I), it can be seen that the relationship between the molecular weight distribution (Mw / Mn) and the weight average molecular weight (Mw) of polyether nitrile having a half crystallization time of 85 seconds or less at a temperature of 275°C can be expressed by formula (ii): The relationship between the molecular weight distribution (Mw / Mn) and the weight average molecular weight (Mw) of the polyether nitrile having a crystallization half time of 50 seconds or less at a temperature of 275° C. can be expressed by formula (iii).

[0196] Formula (ii): Mw / Mn≧2.4×10 -4 ×Mw-11.4 Formula (iii): Mw / Mn≧2.4×10 -4 ×Mw-10.4 Table 5 summarizes the crystallization half time at 275° C., Mw / Mn, the calculated values ​​on the right side of equations (i) to (iii), and whether or not equations (i) to (iii) were satisfied for the polyether nitriles of Examples 1 to 3 and Comparative Examples 1 to 5.

[0197] In the columns “Satisfies Formula (i)”, “Satisfies Formula (ii)”, and “Satisfies Formula (iii)” in Table 5, “0” means that the formula is satisfied, and “×” means that the formula is not satisfied.

[0198] [Table 5]

[0199] It can be seen that among the polyether nitriles of the present invention having a semi-crystallization time of less than 100 seconds at 275° C., the polyether nitriles of Examples 1 and 2 satisfy the relationships of formulae (i) and (ii), the polyether nitriles of Example 3 satisfy the relationships of formulae (i) to (iii), and the polyether nitriles of Comparative Examples 1 to 5 having a semi-crystallization time of more than 100 seconds at 275° C. do not satisfy any of the relationships of formulae (i) to (iii).

[0200] Anyone with common sense in the field of polyether nitrile can understand that since the polyether nitrile in the above embodiment is made of biphenol-polyether nitrile with a slower crystallization rate, various polyether nitrile such as resorcinol-polyether nitrile or hydroquinone-polyether nitrile with a faster crystallization rate are included in the present invention, and are polyether nitrile with a very short semi-crystallization time and a very fast crystallization rate. In addition, it is easy for those skilled in the art to think of applying the technology of the present invention to other polyether resins that are difficult to crystallize, which can be known from the present invention.

Claims

1. A polyether nitrile, characterized in that The semi-crystallization time at 275° C. obtained by input compensation differential scanning calorimetry when the temperature is lowered from a molten state of 370° C. to 275° C. at a cooling rate of 500° C. per minute is 100 seconds or less.

2. The polyether nitrile according to claim 1, characterized in that The polystyrene-equivalent weight average molecular weight (Mw) measured by gel permeation chromatography is 50,000 or more.

3. The polyether nitrile according to claim 2, characterized in that The weight average molecular weight (Mw) and number average molecular weight (Mn) in terms of polystyrene determined by gel permeation chromatography analysis satisfy the formula (i), Formula (i): Mw / Mn≧2.4×10 -4 ×Mw-11.

8.

4. The polyether nitrile according to any one of claims 1 to 3, characterized in that The polyether nitrile has a repeating unit represented by the general formula (3), [Chemistry 1] In the formula, R represents a divalent group represented by the general formula (1a) or the general formula (1b), and r represents an integer of 1 to 4. [Chemistry 2] In the formula, R1 each independently represents a linear or branched alkyl group having 1 to 6 carbon atoms, a cyclic alkyl group having 5 or 6 carbon atoms, or a phenyl group, m each independently represents an integer of 0 to 4, n represents 0 or 1, p and q represent 0, 1 or 2, and * each represents a bonding position, [Chemistry 3] In the formula, R1 and m are the same as defined in the general formula (1a), Y represents an oxygen atom, a sulfur atom, a sulfonyl group, a carbonyl group, an alkylidene group having 1 to 15 carbon atoms, a fluorine-containing alkylidene group having 2 to 15 carbon atoms, a cycloalkylidene group having 5 to 15 carbon atoms, a phenylmethylidene group, a phenylethylidene group, a phenylene group or a fluorenylidene group, Z represents an oxygen atom, a sulfur atom or is unbridged, Ar each independently represents an aromatic group having 6 to 8 carbon atoms, and * each represents a bonding position.

5. The polyether nitrile according to claim 4, characterized in that In the general formula (3), R is the general formula (1a') or the general formula (1a"), [Chemistry 4] In the formula, R1, m and * have the same definitions as those in the general formula (1a). [Chemistry 5] In the formula, R1, m and * are the same as defined in the above general formula (1a).

6. The polyether nitrile according to claim 5, characterized in that The repeating unit represented by the general formula (3) is a repeating unit represented by the general formula (3'), [Chemistry 6] In the formula, R has the same definition as in the general formula (3).

7. The polyether nitrile according to claim 6, characterized in that R of the repeating unit represented by the general formula (3') is at least one group selected from the divalent groups represented by the following structures: [Chemistry 7] 。 8. A polyether nitrile resin composition, characterized in that The invention comprises the polyether nitrile according to claim 1 and at least one selected from the group consisting of (A) to (C) of a thermoplastic resin material (A), an additive (B), and a filler (C).

9. A method for producing the polyether nitrile according to claim 1, characterized in that: Two or more raw material polyether nitriles having different weight average molecular weights are mixed.

10. The method for producing polyether nitrile according to claim 9, characterized in that: The polyether nitrile has a repeating unit represented by the general formula (3), [Chemistry 8] In the formula, R represents a divalent group represented by the general formula (1a) or the general formula (1b), and r represents an integer of 1 to 4. [Chemistry 9] In the formula, R1 each independently represents a linear or branched alkyl group having 1 to 6 carbon atoms, a cyclic alkyl group having 5 or 6 carbon atoms, or a phenyl group, m each independently represents an integer of 0 to 4, n represents 0 or 1, p and q represent 0, 1 or 2, and * each represents a bonding position, [Chemistry 10] In the formula, R1 and m are the same as defined in the general formula (1a), Y represents an oxygen atom, a sulfur atom, a sulfonyl group, a carbonyl group, an alkylidene group having 1 to 15 carbon atoms, a fluorine-containing alkylidene group having 2 to 15 carbon atoms, a cycloalkylidene group having 5 to 15 carbon atoms, a phenylmethylidene group, a phenylethylidene group, a phenylene group or a fluorenylidene group, Z represents an oxygen atom, a sulfur atom or is unbridged, Ar each independently represents an aromatic group having 6 to 8 carbon atoms, and * each represents a bonding position.

11. The method for producing polyether nitrile according to claim 10, characterized in that: The two or more raw material polyether nitriles having different weight average molecular weights are raw material polyether nitriles each having the same repeating unit in the repeating unit represented by the general formula (3).

12. A method for producing a polyether nitrile resin composition, characterized in that: Two or more raw material polyether nitriles having different weight average molecular weights are mixed with at least one of (A) to (C) selected from a thermoplastic resin material (A), an additive (B), and a filler (C), wherein when the two or more raw material polyether nitriles are mixed, the polyether nitrile has a crystallization half time of 100 seconds or less at 275° C. when cooled from a molten state of 370° C. to 275° C. at a cooling rate of 500° C. per minute as determined by input compensation differential scanning calorimetry.

13. The method for producing a polyether nitrile resin composition according to claim 12, characterized in that: The method comprises a polyether nitrile mixing step and a resin composition component mixing step. The polyether nitrile mixing step is a step of mixing the two or more raw material polyether nitriles having different weight average molecular weights to obtain a polyether nitrile, wherein the polyether nitrile has a crystallization half time of 100 seconds or less at 275° C. when cooled from a molten state of 370° C. to 275° C. at a cooling rate of 500° C. per minute as determined by input compensation differential scanning calorimetry. The resin composition component mixing step is a step of mixing the polyether nitrile obtained in the polyether nitrile mixing step with at least one selected from the group consisting of (A) to (C) of the thermoplastic resin material (A), the additive (B), and the filler (C).

Citation Information

Patent Citations

  • Polyarylnitrile polymer and manufacture

    JP1984206433A

  • Novel polymer and its production

    JP1985147439A

  • Novel cyanoaryl ether polymer and its production

    JP1986055120A

  • Novel polymer and its production

    JP1987223226A

  • Molding resin composition

    JP1987240353A